Genetic association of APOB polymorphisms with variation in serum lipid profile among the Kuwait population - Al-Bustan, Suzanne A (BioMed Central, 2014)
BACKGROUND: Several studies have identified APOB as a candidate gene predisposing individuals to dyslipidemia. Polymorphisms including the signal peptide (rs11279109), codon 2488 XbaI (rs1042031), codon 3611 MspI (rs693), codon 4154 EcoRI (rs1801701) and the 3’ variable number of tandem repeats have been reported to be associated with dyslipidemia in several populations. With limited studies on Arabs, this study aimed to investigate the genetic association of APOB polymorphisms and assess the potential influence of minor and rare alleles on serum lipid levels in the Kuwaiti population. METHODS: A total of 795 Kuwaiti subjects, documented with phenotypic data and fasting serum lipid levels, were genotyped for the five polymorphisms using PCR, PCR-RFLP and gene fragment analysis. Genotype and allele association with variation in serum lipid levels as well as haplotypes were analyzed using chi-square test, univariate and logistic regression analysis. RESULTS: Analysis of the genotype and allele frequencies distribution revealed a significant positive association between the APOB signal peptide and 3611 MspI polymorphisms with increased levels of triglycerides (statistical power of 80%). Haplotype analysis further supported the findings by showing that carriers of haplotypes (IX(−)M(−)E(+)M) had significantly lower mean (SD) TG levels (0.86 ± 0.07) as compared to non-carriers (1.01 ± 0.02). Significance was also observed with regards to positive family history of hypercholesterolemia. CONCLUSION: The results imply a “protective role” for two alleles (rs11279109 and rs1801701) in which logistic regression analysis showed a significant half–fold decrease in the risk for heterozygotes of rs11279109 and an 8.8 fold decrease in the risk for homozygous M(−)M(−) of rs1801701 of having lower TG levels (<1.70 mmol/L) in individuals. This suggests that genetic interaction between various polymorphisms at different gene loci act in linkage disequilibrium to affect serum TG levels. Apo B genotyping may be a useful adjunct for the identification of individuals at risk of developing dyslipidemia in order to provide them with lifestyle modifications and/or pharmacological intervention to mitigate the effects of gene interaction and environmental influence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1476-511X-13-157) contains supplementary material, which is available to authorized users.